Nonlinear electrostatic structures and stopbands in a three-component magnetosheath plasma - Rufai, O. R.; Singh, S.V.; Lakhina, G. S. (My University, 2023)
Large amplitude parallel propagating electric field structures of nonlinear electron-acoustic waves are examined in an unmagnetized magnetosheath plasma. Based on the observations and simulations by Ergun et al. (2016), the plasma in the magnetosheath side of the ion diffusion layer is modeled by a 3-component adiabatic fluid dynamic plasma consisting of cold magnetospheric (MSP) electrons, magnetosheath electrons, and background ions. Using the Sagdeev pseudopotential technique, for the plasma parameters recorded by the Magnetospheric Multiscale (MMS) mission in the magnetosheath side of the ion diffusion region, existence regime of the nonlinear electrostatic solitary wave structures is obtained with the possibilities of stopbands (forbidden gap region). Stopbands or the forbidden gap region exists even when the drift velocity of the cold electron beam is zero. The forbidden gap region becomes wider and the Mach numbers of the regions supporting solitary structures become larger by an increase in the drift velocity of the cold electron beam. The results are in agreement with the magnetosheath electrostatic waves having amplitudes of 100s mV/m and frequencies up to 3.2 kHz observed by the MMS.
Keywords: Nonlinear electrostatic structures; Magnetosheath plasma